The lateral supramalleolar flap: a reliable option for lower leg and foot reconstruction - Goil, Pradeep; Sharma, Pankaj; Midya, Manojit; Prakash, Gautam (International Journal of Research in Orthopaedics, 2018)
Background: The lateral supramalleolar flap is based on a perforator of the peroneal artery, emanating at approximately 5 cm above the lateral malleolus on the anterior aspect of lower third leg. Methods: Our technique of harvesting the supramalleolar flap is by using a fasciocutaneous pedicle and minimal perforator dissection. We have done 45 cases in the last 7 years and have got favourable results with this technique. Results: We have not had a single case of total flap necrosis of a supramalleolar flap in our experience over the last 7 years. We routinely perform this flap when the reverse sural flap territory is not available. Conclusions: The lateral supramalleolar flap is a useful flap for coverage of lower third leg, ankle and dorsal foot defects. If raised as described, the reliability of this flap is increased.